A Panel Threshold Analysis of the Impact of Renewable and Non-Renewable Energy Consumption on Economic Growth in Selected MENA Countries - Selmey, Mousa Gowfal; Kammoun, Ali Abdelbasset; Elgohari, Mohamed Ibrahim; Sheta, Ibrahim Hamdy (International Journal of Energy Economics and Policy, 2026)
The study investigates the impact of renewable and non-renewable energy consumption on economic growth in the Middle East and North Africa from 1996 to 2023. The research uses the threshold model methodology to determine the relationship between energy consumption and economic growth, based on GDP, non-renewable energy consumption, and renewable energy consumption. The findings show that the influence of the new energy transition threshold on economic growth depends on the levels of gross domestic product, renewable energy consumption, and fossil fuel energy consumption. The study concludes that the impact of renewable and non-renewable energy consumption on economic growth is non-linear, varying with levels of these factors. The evidence suggests that the behaviours of renewable and nonrenewable energies are similar, which may indicate that the economy is at a single structural level and that structural transformation has not been sufficiently robust. The interaction between renewable and non-renewable energy and economic growth is not restricted to a specific threshold, as each threshold level represents different dimensions of the economic dynamics of the countries. In brief, Heavy reliance on traditional energy sources will result in significant economic resistance, which will negatively impact economic growth. However, with improved renewable energy infrastructure and reduced reliance on traditional or non-renewable energy, this negative impact will transform into a positive effect on long-term economic growth.